MIXED SMALL-SIDED GAMES TRAINING: A STRATEGY FOR IMPROVING ALACTIC ANAEROBIC CAPACITY - Muhammad Ichsannoor Akmal; Iman Imanudin; Mohammad Zaky (RADJA PUBLIKA, 2025)
This study aimed to examine the effect of mixed-method Small-Sided Games (SSG) training on the improvement of alactic anaerobic capacity among adolescent football players. Utilising a pre-test and post-test experimental design, thirty-eight participants aged 12 to 18 years from the Persib Academy underwent a six-week mixed SSG training protocol, three times per week. The intervention systematically varied intensity, duration, and game scenarios to maximise physiological adaptation. Alactic anaerobic capacity was assessed using the Running-based Anaerobic Sprint Test (RAST). Descriptive and inferential analyses revealed statistically significant increases in maximal power, mean power, and fatigue index after the intervention (p < 0.001), with very large effect sizes. These findings highlight the effectiveness of structured mixed SSG training for improving anaerobic performance in youth footballers. The study recommends incorporating mixed SSG approaches in regular training regimens to optimise physical development and support evidence-based coaching practices. These results demonstrate the substantial benefits of mixed-method SSG training for enhancing anaerobic capacity. Nevertheless, future studies are recommended to incorporate a control group and examine long-term effects across diverse youth populations.